2020
DOI: 10.1101/gr.255026.119
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive analysis of indels in whole-genome microsatellite regions and microsatellite instability across 21 cancer types

Abstract: Service Email Alerting click here. top right corner of the article or Receive free email alerts when new articles cite this article-sign up in the box at the http://genome.cshlp.org/subscriptions

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
51
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 67 publications
(56 citation statements)
references
References 57 publications
4
51
0
1
Order By: Relevance
“…In accordance with previous large-scale sequencing efforts in CRC, MSI was evident in our WGS data as the MSI tumors harbored the most indels in repeat regions (Supplementary Table 3). [8][9][10]12,28,29,31,33,34,41,43,44 Instability of tetranucleotide repeats was observed in all 18 MSI CRCs as anticipated (Figure 1A). 14,20,23 Indels in CRCs exhibiting MSI have been reported to occur most prominently in mononucleotide repeats, but also in other short repeats.…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…In accordance with previous large-scale sequencing efforts in CRC, MSI was evident in our WGS data as the MSI tumors harbored the most indels in repeat regions (Supplementary Table 3). [8][9][10]12,28,29,31,33,34,41,43,44 Instability of tetranucleotide repeats was observed in all 18 MSI CRCs as anticipated (Figure 1A). 14,20,23 Indels in CRCs exhibiting MSI have been reported to occur most prominently in mononucleotide repeats, but also in other short repeats.…”
Section: Discussionsupporting
confidence: 79%
“…Largescale sequencing studies on CRC have confirmed MSI CRCs to be a distinct subset of CRC with a large number of mutations, especially indels in their short tandem repeats. [8][9][10]12,28,29,31,33,34,41 To our knowledge, however, EMAST has not been studied on the genomewide level before. Hence, in order to gain a comprehensive picture of tetranucleotide repeat instability in CRC, we utilized WGS data from 227 MSS CRCs, 18 MSI CRCs, 3 POLE-mutated CRCs, and their respective normal samples.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Meanwhile, however, researchers have yet to account for simple sequence repeats with repeated units of dinucleotides (SRs), which are somewhat similar to HPs and are frequently observed in longer barcodes (e.g., 8–12 mer). In this reason, SR is another possible source of errors in PCR amplification and sequencing steps as previously reported [ 24 ].…”
Section: Introductionmentioning
confidence: 84%
“…Annotation of UTRs was performed using ANNOVAR (Wang et al 2010). We also annotated insertions for micro-satellites using an in-house comprehensive list of microsatellites (Fujimoto et al 2020). For ltering out insertions which were possibly false positives due to misalignments of short reads, we applied a ltering strategy similar to the one used in our previous study (Wong et al 2019).…”
Section: Filtering Insertion Candidates Based On Their Annotationsmentioning
confidence: 99%